The Argonautika - Apollonius (Univ. of California Press, 1997)
Jason and the Argonauts' quest for the Golden Fleece is probably the oldest extant Greek myth. Homer referred to it as something
Übers. aus dem Griech.
Keywords: Apollonius <Rhodius>; Argonautica; Argonauts (Greek mythology); Epic poetry; Greek; Jason (Greek mythology); Medea (Greek mythology)